Pengembangan Media Pembelajaran Power Point Ispring Suite 11 Berbantuan Quizizz - Widhianingtyas, Livian; Yudiono, Udik; Indawati, Ninik (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This study aims to create learning media using Ispring Suite 11 PowerPoint for the Economics subject in Class X Social Sciences at SMA Negeri 6 Malang, focusing specifically on Financial Institutions material. The research employs the ADDIE development model (Research and Development/R&D) introduced by Dick and Carey, which includes five phases: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation. The developed media was evaluated by media experts, content experts, language experts, and 35 students. Data collected were both qualitative and quantitative, gathered through observations, Q&A, validation sheets, and student questionnaires. The results show that the innovative learning media, based on Ispring Suite 11 PowerPoint, received a validation rating of 81.2% from material experts, categorizing it as highly feasible, and 85% from media experts, also in the highly feasible category.